Beyond Repression: Reorienting Samapta Authority in Brawl Control in West Java - Muchammad Zafata Ilhamda; Haidan Angga Kusumah (International Forum of Researchers and Lecturers, 2026)
Brawls in West Java represent a persistent form of collective street crime that threatens public order, child protection, and police legitimacy. This article examines Samapta’s legal role in preventing brawls and identifies barriers affecting its implementation. Using empirical juridical research with statutory, conceptual, and socio-legal approaches, the study collects primary data through interviews, operational observations, and institutional documents from the West Java Regional Police, supported by secondary legal and academic sources. Data were analyzed qualitatively using authority theory and Soerjono Soekanto’s five-factor model of legal effectiveness, with triangulation to strengthen validity. The findings indicate that Samapta’s authority is normatively comprehensive based on police laws, organizational regulations, and operational procedures. However, implementation remains uneven due to the dominance of repressive measures, limited resources, communication constraints, and weak post-operation accountability. Barriers involve legal substance, personnel capacity, facilities, community participation, and violent subcultures. The study argues that brawl control requires a shift from incident suppression toward preventive governance through procedural accountability, integrated communication, community-based early warning systems, peace education, and responsive police regulations. This article proposes an ecosystem model integrating patrol, crowd control, public trust, and cultural transformation as interconnected elements of street-crime governance.